Comparison of rapid testing methods for enzyme production with the germ tube method for presumptive identification of Candida albicans. - Heelan, J S (1996)
The observation of germ tube production as a method for the presumptive identification of Candida albicans has been in use for many years. Methods have recently been developed for detecting the production of the enzymes L-proline aminopeptidase and beta-galactosaminidase by yeast isolates grown in culture. Both enzymes are produced by C. albicans; other yeasts may produce either L-proline aminopeptidase or beta-galactosaminidase but not both enzymes. One hundred thirty-three clinical yeast isolates, including 55 C. albicans, 27 Candida tropicalis, 22 Torulopsis (Candida) glabrata, and 29 other yeast isolates were tested by the germ tube production method and three tests for enzyme production, with the API 20C method used as a "gold standard." All three enzymatic methods evaluated provided more objective and rapid nonmicroscopic alternatives to the germ tube test and may be used to accurately distinguish C. albicans from other yeasts.